Description of Work Fatigue of Traditional Weavers in The Weaving Industry of St. Maria Boro Yogyakarta - Theresia Sutinah; Noorce Christiani Berek; Agus Setyobudi (Lontar : Journal of Community Health, 2020)
Fatigue at work is an occupational health and safety problem. Internal and external factors affect work fatigue. Internal factors relate to workers' characteristics, while external factors include unconducive work and work environment. This study purposed to describe the work fatigue of traditional workers in the St. Maria Boro weaving industry, Yogyakarta. This type of research is a descriptive survey. The research population and samples were all 48 workers in the St. Maria Boro Yogyakarta Weaving Industry. Data collection of work fatigue used a questionnaire to measure the feelings of work fatigue (KAUPKK). The results showed that the level of work fatigue significantly felt by workers was tired (83.33%). Regular physical exercise (gymnastics) for the workforce is necessary to reduce work fatigue.